Kadar VCAM-1 Darah Tepi Dan Wilkins Score Pada Stenosis Mitral Penyakit Jantung Rematik - Romi Ermawan (Faculty of Medicine Universitas Mataram, 2022)
Abstract Background: Vascular cell adhesion molecule-1 (VCAM-1) is an important protein in the progression of mitral valve damage in rheumatic heart disease. To measure the severity of the damage, there is a scoring system known as Wilkins Score, consisting of valve mobility disorder, valve thickening, valve calcification and sub-valvular thickening. Methods: This analytic-observational study was using cross-sectional design. There were 45 patients with mitral stenosis of rheumatic heart disease who were collected by consecutive sampling. The peripheral VCAM-1 level was obtained from peripheral venous access, and echocardiogram was obtained to assess Wilkin Score as well as other related parameters. There were also 22 normal subjects who got involved as comparison. Results: The mean Wilkins Score of patients are 9,09 ± 1,81. The mean peripheral VCAM-1 level of patients and normal subjects are 1155,3 ± 328,8 ng/mL and 605,5 ± 100,4 ng/mL. There is significant difference in peripheral VCAM-1 level between 2 groups (p<0,001). There are also significant positive correlations between peripheral VCAM-1 level and valve mobility disorder (p<0,001, r = +0,522), valve thickening (p<0,001, r = +0,583), valve calcification (p<0,001, r = +0,538), sub-valvular thickening (p <0,001, r = +0,647), and also Wilkin Score (p<0,001, r = +0,841). Conclusion: There is a significant positive correlation between peripheral VCAM-1 level and Wilkins Score in mitral stenosis of rheumatic heart disease. Keyword: VCAM-1 - Wilkins Score - Mitral Stenosis - Rheumatic Heart Disease